(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Analytical solution of thermal diffusion and diffusion thermo effects on MHD Casson fluid flow past an oscillating inclined plate embedded through porous medium in the presence of thermal radiation, aligned magnetic field and chemical reaction is obtained. The governing non-dimensional equations are solved using perturbation technique and the solutions are presented in closed form. In order to get a perfect understanding of the physics of the problem we obtained numerical results using Matlab software and clarified with the help of graphical illustrations. With the help of velocity, temperature and concentration, Skin friction, Nusselt number and Sherwood number are obtained and represent through tabular form. Casson parameter is inversely proportional to the yield stress and it is observed that for the large value of Casson parameter, the fluid is close to the Newtonian fluid where the velocity is less than the non-Newtonian fluid.The intensification in values of Soret number produces a raise in the mass buoyancy force which results an increase in the value of velocity.Comparison of the results presented. We have an excellent agreement with the existed results.